MONEY POLITIK PADA KEPEMILUAN DI INDONESIA - M Eza Helyatha Begouvic; Bayu Cuan (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
Abstract: Money politics is the biggest scourge in every political recruitment, including in regional head elections (pilkada). Through the elections, it is hoped that qualified regional leaders will be elected in accordance with the will of the people, but in its implementation, one of the